Emotional exhaustion sebagai Mediator antara Emotional labor dan Job satisfaction Pada Karyawan Sales Ritel - Dewi, Renita; Parahyanti, Endang (Jurnal Psikologi Integratif, 2022)
Many studies have discussed the relationship between emotional labor and job satisfaction, but only few have discussed the role of emotional exhaustion as a mediator in this relationship, especially among retail sales person. This study aims to examine the relationship of emotional labor and job satisfaction through the mediation role of emotional exhaustion. Data for this study was collected from 86 retail sales person from Jabodetabek, recruited through convenience sampling technique. The measurement tools were Job in General, Emotional labor Scale, and Maslach Burnout Inventory. The mediation analysis showed that emotional exhaustion is able to mediate the relationship between surface acting and job satisfaction. However, there was no mediating role of emotional exhaustion in the relationship between deep acting and job satisfaction. These explain that the more retail sales people use surface acting, the more they feel emotional exhaustion which will result in low level of job satisfaction. But those deep acting strategies are not proven to have an influence on emotional exhaustion, so this factor cannot be the mediator in relationship between emotional labor and job satisfaction. Banyak studi sebelumnya yang meneliti hubungan antara emotional labor dan job satisfaction, namun masih sedikit yang membahas terkait peran emotional exhaustion sebagai mediator dalam hubungan tersebut, terutama pada karyawan sales ritel. Penelitian ini bertujuan untuk melihat hubungan emotional labor dan job satisfaction melalui peran mediasi emotional exhaustion. Partisipan penelitian merupakan karyawan sales ritel Jabodetabek yang berjumlah 86 orang, direkrut dengan teknik convenience sampling. Alat ukur yang digunakan dalam penelitian adalah Job in General, Emotional labor Scale, dan Maslach Burnout Inventory. Hasil analisis mediasi menunjukkan bahwa emotional exhaustion mampu memediasi hubungan antara surface acting dan job satisfaction, namun tidak menemukan adanya peran mediasi emotional exhaustion dalam hubungan antara deep acting dan job satisfaction. Ini menjelaskan semakin sering karyawan sales ritel menggunakan surface acting maka semakin karyawan akan merasakan emotional exhaustion yang berdampak pada rendahnya tingkat job satisfaction. Tetapi strategi deep acting yang digunakan karyawan, tidak terbukti memiliki pengaruh terhadap emotional exhaustion, sehingga faktor tersebut tidak dapat berperan sebagai mediator dalam hubungan antara emotional labor dan job satisfaction.